Unveiling the role of cellulose solvent systems in direct and sustainable silica amination: a new pathway beyond aminopropyl agents - Ajiz, Hendrix Abdul; Widiyastuti, Widiyastuti; Setyawan, Heru; Muljani, Srie; Suryandari, Ade Sonya; Erliyanti, Nove Kartika (Universitas Lambung Mangkurat, 2025)
The functionalization of silica surfaces using sustainable amine sources is critical for advancing environmentally friendly materials in CO2 capture technologies. In this study, bio-based organosilanes derived from coconut fiber cellulose were explored as a green alternative to conventional aminosilane. Two solvent systems DMSO/NH4OH and NaOH/urea were utilized to dissolve and regenerate cellulose, enabling direct grafting onto silica surfaces. Comparative analysis revealed that while DMSO/NH4OH-dissolved cellulose exhibited a modest amine loading of 23.43% wt, comparable to aminopropyl-based modification (22.41% wt), the NaOH/urea system significantly improved the grafting efficiency, reaching 40.52% wt. This enhancement is attributed to urea’s amphiphilic properties, which facilitate both hydrophobic interactions and carbamate formation. The use of a sulfur-free NaOH/urea system not only improves performance but also aligns with green chemistry principles. These results demonstrate the potential of biomass-derived cellulose as a viable modifying agent for silica, paving the way for scalable, low-toxicity, and circular-economy-based material design strategies.